Patient profile in emergency departments: Implications for resource management and service planning: Perfil de pacientes atendidos en urgencias: Implicaciones para la gestión de recursos y la planificación de servicios - Prudencio-Leon, Walter Enrique (2025)
Objective: To determine the epidemiological characteristics of emergency department  visits at a private hospital from 2021 to 2023. Materials and methods: This was a retrospective observational study analyzing emergency department visit patterns. Data was extracted from the institution's administrative database. Variables included: ICD-X diagnosis, sex, age, priority level, and period of care. Statistical analysis was performed using Microsoft Excel 365 and Stata v.18.0. Results: Between 2021 and 2023, an average of 72.7 visits per day (95% CI:72.5-72.8) were recorded. Of these, 36.8% involved the pediatric population and 63.2% the adult population. There was higher demand for care in November, December, and January, and Mondays consistently showed the highest number of visits (16.8%). According to the ICD-X classification, Diseases of the Respiratory System (22%) and Injury, Poisoning, and Certain Other Consequences of External Causes (20%) were the most frequent diagnoses among recorded visits. Regarding healthcare coverage, 95% of visits were covered by some type of insurance. For patient discharge, 94.5% of patients were discharged to their homes. Furthermore, the following priority-based service rates were observed: 13.8 per 1000 visits for Priority I and 198.4 per 1000 visits for Priority II. Conclusions: The emergency department predominantly serves an adult population presenting with conditions that are resolved on the same day of care. Keywords: Emergency Service, Hospital; Emergency Medical Services; Epidemiology; Emergency Room Visits (Source: MeSH, NLM).